PAJAK KARBON SEBAGAI SUMBER PENERIMAAN NEGARA DAN SISTEM PEMUNGUTANNYA - Agustinus Imam Saputra (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2021)
The study aims to elaborate on carbon taxes as a potential source of state revenue. This study also provides an overview of the imposition of excise rates that can be applied in Indonesia. Besides, this study tries to look deeper into the procedures for reporting and monitoring excise tax paid by taxpayers. This research uses descriptive qualitative research methods. A review of documents and regulations related to carbon emissions in Indonesia and other countries is an important source. The study was conducted by comparing best practices in several countries with Indonesia regarding government policies regarding carbon tax policies. The study results show that there is potential for state revenue from carbon taxes. On the other hand, the collection of carbon taxes requires a system-integrated procedure between the Ministry of Finance and the Ministry of Environment and Forestry. Therefore, digitizing the system and establishing a data warehouse is important to support the Directorate General of Customs and Excise (DGCE) as the excise collection authority. An important finding in this study's conclusion is the urgent need for regulations to implement a carbon tax in Indonesia. In the future, this research is expected to trigger further research on carbon taxes and their effects on national economic growth.